Idols within Our Lady of the Rosary Church - Mumbai Archive Project Team (Jio Institute, 2024)
During the vicarship of Stanislaus Pereira, Our Lady of the Rosary church underwent extensive interior and exterior refurbishment to achieve a more contemporary appearance. Msgr Stanislaus, who served at Our Lady of the Rosary for nearly 20 years (1953-1974), implemented many changes for the benefit of the parishioners.